The characteristics of offensive actions of Spanish national team in 2010 football world championship in south africa - Buraczewski, T.; Cicirko, L.; Irla, L.; Twarowski, K. (7th World Congress on Science and Football (WCSF), 2011, 2011)
In order to facilitate the process of teaching and improving a football game, enhancing the effectiveness of training, increasing the efficiency of players, permanent gathering information about footballers is indispensable. Determining characteristic features of offensive actions performed by the Spanish national team during 2010 World Championship in South Africa is undoubtedly a very important aspect. Methods The research material comprised the observation of seven football games of Spanish team in 2010 World Champion Finals. The registration was made taking following points into account: the way of winning the ball: interceptions, in 1x1 duel; the type of the action: after the fast attack, positional attack or the one after the set play; the characteristic of the action taking into account the time of the action as well as the number of passes and the number of players who participated in it; the way of performing the last pass: direction, length and the way of performance; the way of scoring the goal: right leg and the head, left leg and the head; the distance from which goals were scored (fields zones); technique as well as the way of kicking the ball. During the observation of the matches the analysis of 123 offensive actions was made. Results & Discussion The results of the offensive actions ended with the shot at the goal, which consider the time of their performance, the number of passes and the number of participants prove that the most successful actions consisted of a small number of passes (1-3), in which up to 4 players took part, and they lasted up to 15 seconds. The obtained data correspond with other research (Bergier, Buraczewski 2007, Armatas et al. 2007, Acar et al. 2009). The analysis resulted in the statement that actions ended with the shot from a long distance are not very effective. Conclusion The research results should constitute an important impulse to rationalize the training process, which indicates a need to practise shots at the goal from the penalty area after short combinations of passes. The analysis of obtained results indicates an applicational aspect of football training with reference to the rationalization of the choice of exercises in the training process and its optimization.